2013
DOI: 10.1007/s10802-012-9708-6
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Shyness-Sensitivity and Internalizing Problems in Chinese Children: Moderating Effects of Academic Achievement

Abstract: Shy-sensitive children are likely to develop adjustment problems in today's urban China as the country has evolved into an increasingly competitive, market-oriented society. The main purpose of this one-year longitudinal study was to examine the moderating effects of academic achievement on relations between shyness-sensitivity and later internalizing problems in Chinese children. A sample of 1171 school-age children (591 boys, 580 girls) in China, initially at the age of 9 years, participated in the study. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 45 publications
8
77
0
Order By: Relevance
“…The average score of the responses was computed and used in the analysis, with higher scores indicating greater loneliness. The measure has proved reliable and valid in Chinese children (e.g., Chen et al 2013). The internal consistency of the measure was 0.91 in the present study.…”
Section: Measures In the Follow Up Study (11 Years)supporting
confidence: 59%
See 1 more Smart Citation
“…The average score of the responses was computed and used in the analysis, with higher scores indicating greater loneliness. The measure has proved reliable and valid in Chinese children (e.g., Chen et al 2013). The internal consistency of the measure was 0.91 in the present study.…”
Section: Measures In the Follow Up Study (11 Years)supporting
confidence: 59%
“…The items were scored 0, 1, or 2, and mean scores of the items were computed in this study, with higher scores indicating more depressive symptoms. The measure has proved to be reliable and valid in Chinese children (e.g., Chen et al 2013). The internal consistency was 0.81 in the present study.…”
Section: Measures In the Follow Up Study (11 Years)mentioning
confidence: 99%
“…First, consistent with the literature suggesting teachers' awareness of heightened anxiety in shy children (Arbeau & Coplan, ), we found that teachers rated shy children as exhibiting more shy‐anxious behaviour than nonshy peers across all time points. This result is also in line with previous findings suggesting general negative teacher perceptions of shy children in urban areas of China (Chen et al, , ). Moreover, our results provided further evidence that teachers interacted with shy and nonshy children differently in class.…”
Section: Discussionsupporting
confidence: 93%
“…Shy children consistently showed higher levels of reticent behaviour, initiated and engaged in less peer interaction, and were less likely to initiate interaction with and respond to teachers. These findings lend support to previous research (Chen et al, , ; Coplan & Arbeau, ) suggesting elevated risk for adjustment problems in shy children. Despite the consistent differences between shy and nonshy children's observed behaviours, their patterns of adjustment in the context of peer interaction were similar: their reticent behaviour increased and peer interaction decreased at the beginning of the first grade and then returned to normal within a period of 2 months.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, substantive negative implications were anticipated for young children who displayed this subtype of social withdrawal. Moreover, academic achievement may also play a particularly important role in the socio-emotional functioning of withdrawn children in China (Chen, Yang, & Wang, 2013). Problems with peer relations and poor teacher-child relationships are by themselves important indicators of concurrent and future difficulties in socioemotional and academic functioning (e.g., Hamre & Pianta, 2001;Rubin, Bukowski, & Parker, 2006).…”
Section: Validity Of the Adapted Vignettesmentioning
confidence: 99%